Multispecies-ethnography methodology of a holistic research approach of humans, animals, nature, and culture - Ameli, Katharina, 1986- (Lexington Books, 2022)
"This book extends the ethnographic approach to animals and animate and inanimate natures. The focus is on developing a method suitable for holistic and interdisciplinary research, and to fulfill this goal, elements of Human-Animal Studies and NaturesCultures are combined and Indigenous approaches are incorporated"--